Analysis of the causes of damage to centrifugal pumps during operation and methods of their elimination - Morshch, I.V. (Problems of Tribology, 2025)
The paper reviews the research on improving the efficiency of operation and service life of centrifugal pumps, which are widely used in machinery for pumping various liquids. The main reasons for the failure of centrifugal pumps, as well as modern approaches to their prevention, are considered. It is established that increasing the efficiency of pump operation can be achieved by analyzing, modeling and optimizing their design. It was found that modeling the operation of smaller pump models and comparing surrogate models with the original ones is a modern, highly effective method of optimizing pump performance. The important role of protective coatings in increasing the wear resistance of parts is established, and the experience of introducing innovative coating technology at enterprises is described.